(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The effects of daily, weekly and annual academic loads on the hemodynamical and psychophysiological characteristics of the XI class pupils of the city Sari, Republic of Iran, were analyzed. The self-estimated state of health, activity and mood were evaluated using the HAM questionnaire. The introversion and extraversion, neuroticism and intelligence of the subjects were determined according to Eysenck. The main hemodynamic parameters (heart rate and arterial blood pressure) were measured, the systolic and minute blood volumes were calculated. The comparative analysis explored parameters in mode of daily, weekly and annual scholastic load has revealed basically parasympathetic type of reaction of hemodynamical factors of the pupils on scholastic load.